2004
DOI: 10.1136/ip.2004.005389
|View full text |Cite
|
Sign up to set email alerts
|

Construction safety research in the United States: targeting the Hispanic workforce

Abstract: While it is known that Hispanics have a continuous growing participation in the construction workforce and that their fatal and non-fatal occupational injuries are higher than any other ethnic group, very little construction safety and health research has been conducted in the United States. Research that focuses on safety and health of Hispanic workers employed in the construction industry might prove beneficial in reducing injuries and promoting safe and decent workplaces for all.The purpose of this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 9 publications
4
58
0
Order By: Relevance
“…Kameda et al reported that the implementation rate of health and safety education for Japanese temporary workers was approximately 60% 11) , and another previous study reported that the implementation rates of health and safety education were from 55% to 85% in SMEs 12,13) . The rates of safety training for immigrant workers in USA were approximately 30% to 70% [3][4][5] , similar to our results. We considered that these services were conducted for immigrant workers without a margin for comparing with Japanese and American workers.…”
Section: Discussionsupporting
confidence: 81%
“…Kameda et al reported that the implementation rate of health and safety education for Japanese temporary workers was approximately 60% 11) , and another previous study reported that the implementation rates of health and safety education were from 55% to 85% in SMEs 12,13) . The rates of safety training for immigrant workers in USA were approximately 30% to 70% [3][4][5] , similar to our results. We considered that these services were conducted for immigrant workers without a margin for comparing with Japanese and American workers.…”
Section: Discussionsupporting
confidence: 81%
“…Prior research supports higher injury rates for Hispanic and Latino employees, especially in construction and agriculture [McCurdy et al, 2003;Brunette, 2004;Brunette, 2005]. We are currently expanding our collection of data on race and ethnicity and studies of differences by sociodemographic factors are planned.…”
Section: Discussionmentioning
confidence: 94%
“…Pun and her colleagues (41) described an educational intervention to address musculoskeletal concerns with Mandarin-speaking garment workers. They, as well as other authors, pointed out that language is only one of the issues involved (41,42). Safety training and personal protective equipment, though a vital part of workplace health and safety, ultimately focus on the individual worker, rather than addressing and limiting the root causes of exposures and injuries.…”
Section: Prevention-safety Education Training and Personal Protectivmentioning
confidence: 99%